Internalisasi Nilai-Nilai Kristiani dalam Mengatasi Krisis Moralitas di Era Digitalisasi terhadap Pembentukan Karakter Pemuda - Ferry Yeferson Tulle; Fendy Ongko; Juanda Julianus (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2026)
The wave of digitalization triggers a severe morality crisis among the younger generation through constant exposure to negative content, cyberbullying, and global communication ethics degradation. This descriptive qualitative study aims to analyze the specific internalization of Christian values at GPIB Harapan Kasih Congregation Bekasi to shield youth morality amidst ongoing technological disruption. Employing intensive in-depth interviews and participatory observations, data were analyzed interactively through systemic reduction, structured display, and final verification. The results indicate that the digital morality crisis explicitly manifests as pornography normalization, virtual toxicity, and the severe erosion of academic honesty. In response, pastoral strategies utilizing highly contextualized digital ethics sermons and youth cell groups prove thoroughly effective. The deep internalization of self-control and integrity successfully stimulates a holistic self-censorship mechanism across the youth's cognitive, affective, and behavioral domains. This study concludes that consistent accountability-based mentorship effectively transforms Christian youth from passive digital victims into active agents of change within global cyberspace.